Extent of the association between self-rated health and place of birth: a cross-sectional study among people at high risk of developing pre-diabetes and diabetes in Sweden - Claes-Goran Ostenson; Marina Taloyan; Amina Amri; Kristin Hjörleifsdottir Steiner; Fahimeh Lamian; Helena Salminen (BMJ Open)
Objective The first aim was to determine the extent of the relationship between place of birth and self-rated health (SRH) in primary healthcare patients born outside Sweden and those born in Sweden. The second aim was to investigate whether socioeconomic and lifestyle factors explained any differences.Setting Two academic primary healthcare centres in Stockholm County, Sweden.Participants 825 patients at high risk of developing pre-diabetes and diabetes, aged 18–74 years, attending academic healthcare centres in areas with large numbers of immigrants, 56.8% born abroad and 43.2% born in Sweden. Patients with a diagnosis of diabetes were excluded. Inclusion criteria were based on previous research showing that people born in Middle Eastern and Asian countries who live in Sweden have a high prevalence of and risk for diabetes.Outcome SRH was dichotomised as optimal (very good/good) and suboptimal (fair/bad/very bad) and compared in those born outside Sweden and in Sweden.Results There was a statistically significant difference in the SRH of the two groups (p=0.008). Logistic regression analysis showed a crude OR for reduced SRH of 1.46 (95% CI 1.10 to 1.92) in patients born outside Sweden. After controlling for education, employment and marital status, the OR increased to 1.50 (95% CI 1.11 to 2.02). After controlling for physical activity and smoking, it decreased to 1.36 (95% CI 1.00 to 1.85).Conclusion Socioeconomic and lifestyle factors influenced SRH. It could therefore be useful for clinicians to consider these factors when providing care for patients born outside Sweden and resettled in areas with large numbers of immigrants.